Creening Effect in (p, n) Reactions on Heavy Element Targets 82 206Pb, 92 308U, 74184W, 79197Au - Giao, Nguyen Mong; Thu, Nguyen Thi Ai; Truc, Le Thi Thanh (Communications in Physics, 2012)
We present a simple model to calculate multiplicities of the neutrons emitted in the interaction of a proton beam energy from 0.5 GeV to 1.5 GeV on some targets such as 82 206 Pb, 79197Au, 92238U using database of JENDL-HE library. The results are compared with the available experimental data [8]. The agreement is satisfactory